2009
DOI: 10.4062/biomolther.2009.17.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Schizandra chinensis Alkaloids Inhibit Lipopolysaccharide-Induced Inflammatory Responses in BV2 Microglial Cells

Abstract: -Schizandra chinensis (S. chinensis) exhibits a harmless, 'adaptogen-type' effect leading to improvements in mental performance and learning efficacy in brain. Activated microglia contributes to neuronal injury by releasing neurotoxic products, which make it important to regulate microglial activation to prevent further cytological as well as functional brain damage. However, the effect of S. chinensis on microglial activation has not been examined yet. We have investigated the effects of four compounds (Gomis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated the diverse pharmacological activities of S. chinensis, which include anti-oxidant, anti-tumor, anti-obesity, anti-inflammatory, and cardioprotective effects. [11][12][13][14][15] In addition, hepatoprotective activities of S. chinensis have also been reported. [16][17][18][19] A recent study of ours showed that S. chinensis has a protective effect against ER stress-induced hepatic steatosis (unpublished data).…”
mentioning
confidence: 99%
“…Several studies have demonstrated the diverse pharmacological activities of S. chinensis, which include anti-oxidant, anti-tumor, anti-obesity, anti-inflammatory, and cardioprotective effects. [11][12][13][14][15] In addition, hepatoprotective activities of S. chinensis have also been reported. [16][17][18][19] A recent study of ours showed that S. chinensis has a protective effect against ER stress-induced hepatic steatosis (unpublished data).…”
mentioning
confidence: 99%
“…Several studies have demonstrated the diverse pharmacological activities of S. chinensis , including antioxidant11, antitumor12, anti-obesity13, anti-inflammatory14, cardioprotective15, and hepatoprotective effects16. S. chinensis contains various bioactive constituents, including lignans, triterpenoids, polysaccharides, and sterols17.…”
mentioning
confidence: 99%
“…Oh et al have recently reported that when LPS stimulates Raw 264.7 cells, three ingredient of Sc-gomisin J, gomisin N, and schisandrin C-reduced NO production by blocking p38 mitogen-activated protein kinase, extracellular signal-regulated kinases 1 and 2 (ERK 1/2), and c-Jun N-terminal kinase phosphorylation (Oh et al, 2010). Choi et al have recently revealed that four lignans, Gomisin A, Gomisin N, Schizandrin and Schizandrol A, regulate the induction of NO, reactive oxygen species, and matrix metalloproteinase-9 by blockage of ERK 1/2 on LPS-induced BV2 microglial activation (Choi et al, 2009). Guo et al have recently reported that Schisandrin inhibited plasma NO production in vivo (Guo et al, 2008).…”
Section: Discussionmentioning
confidence: 97%